Heme oxygenase-1 determines the cell fate of ferroptotic death of alveolar macrophages in COPD - Li, Yi; Yang, Ying; Guo, Tingting; Weng, Chengxin; Yang, Yongfeng; Wang, Zhoufeng; Zhang, Li; Li, Weimin (Frontiers in Immunology, 2023)
Despite an increasing understanding of chronic obstructive pulmonary disease (COPD) pathogenesis, the mechanisms of diverse cell populations in the human lung remain unknown. Using single-cell RNA sequencing (scRNA-Seq), we can reveal changes within individual cell populations in COPD that are important for disease pathogenesis. We performed scRNA-Seq on lung tissue obtained from donors with non-COPD and mild-to-moderate COPD to identify disease-related genes within different cell types. We testified the findings using qRT‒PCR, immunohistochemistry, immunofluorescence and Western blot from 25 additional subjects and RAW 264.7 macrophages. Targeting ferroptosis with ferroptosis inhibitors, iron chelators or HO-1 inhibitors was administered in the experimental cigarette smoke COPD mouse model. We identified two populations of alveolar macrophages (AMs) in the human lung that were dysregulated in COPD patients. We discovered that M2-like AMs modulate susceptibility to ferroptosis by disrupting lipid and iron homeostasis both in vivo and in vitro. The discrepancy in sensitivity to ferroptosis can be determined and regulated by HO-1. In contrast, M1-like AMs showed the ability to attenuate oxidative stress and exert resistance to ferroptosis. In addition, the expression of genes within M2-like AMs is also involved in defects in phagocytosis and lysosome distortion. This ferroptotic phenotype was ameliorated by anti-ferroptotic compounds, iron chelators and HO-1 inhibitors. During COPD, the accumulation of lipid peroxidation drives ferroptosis-sensitive M2-like AMs, while M1-like AMs show characteristics of ferroptosis resistance. The development of therapeutic strategies specifically targeting ferroptosis-sensitive alveolar macrophages might be used to develop therapeutic targets.